Preventing electrically induced subsurface initiated pitting failures (incl. WSF, WEC, WEA) with copper based lubricant additives - Sergei Mamykin; Marc Ingram; Leyla Alieva; Varvara Privalova (Frontiers in Mechanical Engineering)
Premature bearing failures in large electric machines such as wind turbines and locomotives are often caused by White Etching Cracks (WEC), White Etching Areas (WEA), and White Structure Flaking (WSF)—phenomena that, despite extensive study, remain not fully understood. This work introduces a new hypothesis of WEC, WEA and WSF formation combining Garkunov’s scientific discoveries of “hydrogen wear of metals” and the “wearlessness effect” with the existing knowledge and offers a possible solution. To test this hypothesis and solution, a prototype lubricant containing oil-soluble copper salts was evaluated using an electrically induced WEC test on a three ring-on-roller tribometer. The test applied high contact pressures and direct current to simulate operating conditions, followed by subsurface serial sectioning to examine material degradation. The results showed that the reference lubricant exhibited typical WEC and WEA damage, while the copper-based candidate lubricant prevented such failures entirely. This outcome supports the idea that hydrogen activity plays a central role in damage formation, and that targeted additives can prevent it by reducing surface temperatures and forming protective film, which blocks hydrogen diffusion. These findings offer a scientifically grounded and practically viable solution to extend bearing life and prevent costly failures in high-load, high-reliability applications.